Penerapan Model Discovery Learning untuk Meningkatkan Hasil Belajar Tema 3 Subtema 1 Siswa Kelas VI SD Negeri Bintoro 14 Demak - Mashudi, Mashudi (Jurnal Kualita Pendidikan, 2024)
This study aims to determine the improvement in learning outcomes after implementing the Discovery Learning model in thematic learning theme 3 subtheme 1 in class VI of SD Negeri Bintoro 14 Demak semester I of the 2021/2022 academic year. The subjects of this study were 13 class VI students consisting of 8 male students and 5 female students. The type of research used was classroom action research which was carried out in two cycles. Each cycle was carried out in four stages, namely planning, implementation, observation, and reflection. The data collected in this study were data on student learning outcomes using observation and test methods, then the data obtained were analyzed descriptively. In the pre-cycle, the percentage of student learning outcomes that experienced completeness was only 15.38%, then increased to 53.84% in cycle I and increased again to 84.62% in cycle II. This increase occurred because the teacher had applied the learning model according to its syntax and could encourage students to be actively involved in learning so that students could understand the material freely. Based on this, it can be concluded that the application of the discovery learning model can increase student activity and learning outcomes in thematic learning.